Malpractice litigation, quality improvement, and the University Hospitals Obstetric Quality Network. Issue 5 (October 2019) - Cossler, Nancy; Liu, James; Porter, Steven; Albertini, Megan; Katz, Tyler; Pronovost, Peter
Objective: A healthcare organization's medical malpractice data can help identify patient safety risks and drive improvement. In most organizations, obstetric malpractice losses are assumed to be part of the risk of delivering obstetric care. We describe a systematic approach to mitigating risks for obstetric patients and their newborns while simultaneously improving patient outcomes and reducing obstetric litigation costs at University Hospitals, a northeast Ohio-based health system of 18 hospitals, including seven hospitals providing obstetric services and delivering approximately 8000 women per year. Methods: From multiple data sources, including malpractice claims data, the team identified four key drivers of risk on the obstetric service: hypoxic ischemic encephalopathy, obstetric hemorrhage, hypertensive disorders of pregnancy, and shoulder dystocia. Collectively, these contributed to multiple adverse maternal and neonatal outcomes and accounted for 71% of obstetric litigation costs from 2009 to 2015. In response, the team built a regional obstetric quality network and implemented interventions to mitigate the four major risk areas. Results: We achieved a substantial reduction in serious safety events from 2010 to 2018, defined as any event where the standard of care was not met and the level of harm to mother or baby was one (death) or two (severe permanent or temporary harm). We also achieved a reduction in obstetric litigation costs between 2009–2012 and 2015–2018. Discussion: This multifaceted intervention was associated with decreased patient harm and reduced obstetric litigation costs. Application of this approach to other hospitals could result in improvements in obstetric patient safety and reduced obstetric litigation costs.